THE STUDENT LEARNING MOTIVATING FACTORS ON THE EXAMPLE OF TECHNICAL IT SUBJECTS - Noga, Henryk (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Teacher other than parents, has a decisive influence on the formation of students personality. Students have different motivation to work is which also constantly evolving. Teachers and educators play significant role in the life of a young people life. The primary objective of this paper is to demonstrate the importance of the teacher attitude on the formation of motivation for learning among students. The way a teacher motivates and how it affects students results. It is therefore essential to find those patterns that will allow work a teacher so that his students start to want learn, in the future, make his lessons remembered and find these lessons as interesting as they can be. Teachers should be able to adopt the attitude that in the memories of students will be referred as a positive, learning encouraging and equitable.